2023
DOI: 10.3390/ijms24087585
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin in Ovarian Cancer Treatment—Known Limitations in Therapy Force New Solutions

Abstract: Cisplatin is one of the most commonly used anticancer drugs worldwide. It is mainly used in the treatment of ovarian cancer, but also used in testicular, bladder and lung cancers. The significant advantage of this drug is the multidirectional mechanism of its anticancer action, with the most important direction being damaging the DNA of cancer cells. Unfortunately, cisplatin displays a number of serious disadvantages, including toxicity to the most important organs, such as kidneys, heart, liver and inner ear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 132 publications
0
19
0
Order By: Relevance
“… 1 , 2 Cisplatin was first synthesized by Peyrone in 1845. 3 Its properties were fortuitously discovered in 1965 by Dr. Barnett Rosenberg while observing electric current effects on bacterial growth. 4 , 5 Rosenberg reported that electric fields lead to filamentous growth of Escherichia coli cells.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Cisplatin was first synthesized by Peyrone in 1845. 3 Its properties were fortuitously discovered in 1965 by Dr. Barnett Rosenberg while observing electric current effects on bacterial growth. 4 , 5 Rosenberg reported that electric fields lead to filamentous growth of Escherichia coli cells.…”
Section: Introductionmentioning
confidence: 99%
“…The platinum‐containing compound cisplatin is one of the most widely employed of these agents (Bukowski et al, 2020 ; Qi et al, 2019 ). Cisplatin [ cis ‐diamminedichloroplatinum (II)] was approved as a cancer therapeutic in 1978 (Makovec, 2019 ) and has shown broad‐spectrum effectiveness: it has been used to treat cancers of the lung, ovaries, breast, and brain, among others (Dasari & Tchounwou, 2014 ; Makovec, 2019 ; Zoń & Bednarek, 2023 ). The therapeutic strategy of cisplatin is to target the rapidly dividing DNA of cancer cells, where it binds preferentially to the N7 position of purine bases.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its effectiveness as an affordable standard therapy for various tumors, cisplatin's utility is limited by the development of drug resistance and its accumulation in tissues, which can lead to severe side effects such as neurotoxicity, ototoxicity, and nephrotoxicity (Martinho et al, 1898 ; Messori & Merlino, 2014 ; Mortensen et al, 2020 ; Peleg‐Shulman et al, 2002 ; Zhao et al, 2014 ; Zoń & Bednarek, 2023 ). Several cisplatin analogs have been developed for use in the treatment of cancers (Dasari & Tchounwou, 2014 ; Kopacz‐Bednarska & Król, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is a chemotherapeutic agent widely used in cancer treatment [12] and is considered a representative member of the platinum compound family. Since the 1970s, cisplatin has been widely used to treat a variety of malignancies, including lung, ovarian, bladder, and HCCs [13]. However, a remarkable variation was found in patient response to cisplatin, suggesting a possible underlying molecular mechanism regulating its sensitivity.…”
Section: Introductionmentioning
confidence: 99%